The Impact of Digitalization on Work Patterns and the Protection of Workers' Rights: a Study of Labor Law in the Banking Sector - Djunaidi, Zikri Habibi; Dalimunthe, Nikmah (LPPPIPublishing, 2024)
Digitalization has revolutionized the banking sector by improving efficiency and productivity through the adoption of information technology. While digitalization offers convenience, it also poses new challenges for workers, especially in relation to the reduction of traditional jobs and the need for higher digital skills. This study aims to analyze the impact of digitalization on work patterns and workers' rights in the banking sector, with a focus on time flexibility, outsourcing, and the reduction of manual labor. In addition, the study will analyze existing labor law policies to assess the extent to which they are able to protect workers' rights in the face of these rapid changes. The approach used is qualitative with a descriptive method. Data is analysed using thematic analysis techniques, as well as using a normative-empirical legal approach to assess the relevance of labour policies in the context of digitalization. Validation is done through source triangulation by comparing the findings of this research with previous studies. The results show that digital transformation in the banking sector is changing work patterns with a hybrid model, decreasing the need for manual labor, and increasing the demand for digital skills. The use of outsourced labor is also increasing, but raises worker protection issues. Existing labor regulations need to be updated to respond to these new challenges and ensure the protection of workers' rights.